The Importance of Civilizational Values to the Ourtset, Establishment and Continuation of Civilization (Salam International Academic Journal, 2012)
In this paper, which is a very important research, the author seeks to first clarify the meaning of values. He has then sought to define civilization and have proved that there is difference between absolute values and civilizational values as common values are in fact touchstones for good and evil, correct and incorrect while civilizational values are not only criteria for good and evil, correct and incorrect, but also are deemed as the theoretical principles and bedrocks which are motives for the creation of civilization and make its mental and psychological foundations. All the achievements of civilization are deemed their practical and real interpretation. The characteristics of the civilizational values are as following: They are common and universal values, they are standards for civilization, they are humane values which are not found in other creatures, they enjoy different levels of importance among them, but are complementing each other. Values are very important for a civilization. A civilization cannot be established without values. The importance of values for a civilization could be proved by the facts that values are preceding a civilization in time: values do not disappear by vanishing a civilization; a civilization does not vanish by negating one of its components, however, a civilization disappears by denial of its values. Furthermore, values have impact on all processes and achievements of a civilization.
Keywords: Civilization; Value; Absolute Values; Civilizational Values; Establishment